Effects of clay activation and amine chain length on silica-palygorskite heterostructure properties - Boudriche, L.; Bergaya, F.; Boudjemaa, A.
Various approaches have been used for the preparation of heterostructured materials based on clay minerals, with numerous potential applications offered by the resulting functional materials. In this study, a fibrous clay mineral (palygorskite)and a tetraethyl orthosilicate reagent were used to obtain silica-palygorskite heterostructures. The aim was to highlight the influence of two factors during the preparation process: the effect of acid activation pre-treatment of the palygorskite with HCl and the effect of varying the length of the amine chains used - dodecylamine and butylamine - on the formation and development of silica nanoparticles on the surface of the palygorskite fibres. The silica-palygorskite heterostructures were obtained after the removal of the organic templates by calcination at 500°C. The textural and structural properties of the silica-palygorskite heterostructured samples were determined using various experimental characterization techniques, such as X-ray diffraction, transmission electron microscopy, gas adsorption and Fourier-transform infrared spectroscopy. The experimental variables targeted in this study appeared to have a significant effect on the textural properties of the silica-palygorskite heterostructure obtained. The great specific surface area and the mesoporous, microporous and ultramicroporous volumes as determined using nitrogen and/or carbon dioxide gas adsorption confirm the benefit of combining the acid activation pre-treatment of the fibrous clay mineral with the use of a long-chain amine co-surfactant (dodecylamine). The resulting silica-palygorskite heterostucture has a great specific surface area (628 m2 g-1)and a well-developed total pore network (VN2 = 0.24 cm3 g-1; Vultra (CO2)= 0.18 cm3 g-1). This material will be tested for the removal of volatile organic compounds at low concentrations.
Keywords: ACID TREATMENT; AMINE CHAIN LENGTH; HETEROSTRUCTURE; PALYGORSKITE; PHYSICOCHEMICAL CHARACTERIZATIONS; SILICA NANOPARTICLES